1. Number that adds up to -12 and multiplied by the same # that gives u -13. Set it up like this because both are negative so, u need 1 negative and 1 positive.
(x-13)(x+1)
2. Same rule applies. GCF
8y(4y+1)
3. (x+3)(x-3)
-3x^2-2x (+-)6=0
ax^2+bx+c
a=-3
b=-2
c= either positive or negative 6 (there is no plus or minus in your question.)
What are the answer choices? It might help.
Answer:
52.5
Step-by-step explanation:
it is simple. very simple
Answer:
x = 6
Step-by-step explanation:
8x + 2 + 70 + 60 = 180
8x + 132 = 180
8x = 48
x = 6